Full-length galectin-8 and separate carbohydrate recognition domains: the whole is greater than the sum of its parts? - Cagnoni, Alejandro (2020)
Galectin-8 (Gal-8) is a tandem-repeat type galectin with affinity for β-galactosides, bearing two carbohydrate recognition domains (CRD) connected by a linker peptide. The N- and C-terminal domains (Gal-8N and Gal-8C) share 35% homology, and their glycan ligand specificity is notably dissimilar: while Gal-8N shows strong affinity for α(2-3)-sialylated oligosaccharides, Gal-8C has higher affinity for non-sialylated oligosaccharides, including poly-N-acetyllactosamine and/or A and B blood group structures. Particularly relevant for understanding the biological role of this lectin, full-length Gal-8 can bind cell surface glycoconjugates with broader affinity than the isolated Gal-8N and Gal-8C domains, a trait also described for other tandem-repeat galectins. Herein, we aim to discuss the potential use of separate CRDs in modelling tandem-repeat galectin-8 and its biological functions. For this purpose, we will cover several aspects of the structure?function relationship of this protein including crystallographic structures, glycan specificity, cell function and biological roles, with the ultimate goal of understanding the potential role of each CRD in predicting full-length Gal-8 involvement in relevant biological processes.